A single domain antibody-based Luminex assay for the detection of SARS-CoV-2 in clinical samples - Goldman, Ellen R.; Sugiharto, Victor A.; Shriver-Lake, Lisa C.; Garcia, Andrew M.; Wu, Shuenn-Jue; Jenkins, Sarah A.; Chen, Hua-Wei (Frontiers in Immunology, 2024)
Within the past decade, single domain antibodies (sdAbs) have been recognized as unique affinity binding reagents that can be tailored for performance in a variety of immunoassay formats. Luminex MagPlex color-coded magnetic microspheres provide a high-throughput platform that enables multiplexed immunoassays. We developed a MagPlex bead-based assay for the detection SARS-CoV-2, using sdAbs against SARS-CoV-2 nucleocapsid (N) protein in which we engineered the sdAb capture reagents to orient them on the beads. The oriented sdAbs provided an increase in sensitivity over randomly oriented sdAbs for samples of N diluted in buffer, which also translated into better detection of SARS-CoV-2 in clinical samples. We assessed the specificity of the assay by examining seasonal coronavirus clinical samples. In summary, we provide a proof-of-concept that a bead-based assay using sdAbs to detect SARS-CoV-2 is feasible and future research combining it with other sdAbcoated beads that can detect other viruses may provide a useful diagnostic tool.